A case Study of Fat and Release of Hydrogen in Sewage Sulfide During the Management of Sewage Projects - Hussein, S N; Alrubaye, R F; Nassar, Yasser (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
During sewage projects, management appears Hydrogen sulfide (H2S) emission-related odours have been a problem in sewage project networks for decades. One of the gases that directly harms employees and network infrastructure is hydrogen sulfide gas. Using the TOXCHEM software, the network of the Al-Hur project in Karbala, south of the Iraqi capital, Baghdad, was simulated for three main lines of different diameters 630, 315, and 1000 mm, each with a diameter of 1000 meters, they are connected to a main manhole by drop structure, and then to the lift station. Samples for these diameters were collected for two seasons (summer and winter) with all the necessary parameters of this network to be included in the model. The model was validated for the two seasons, and the results were very close to reality after being examined in a statistical way, where the results of R and RMSE were (0.821 and 0.821) and (0.000462 and 0.000184) for Summer and Winter, respectively. Sensitivity analysis studied wastewater characteristics with different levels of H2S loading rate, flow rate, suspended solid concentration, oil/grease concentration, and temperature. The results showed that all emissions in these networks are dangerous, especially in the summer when the emissions concentrations for pipe 315, pipe 630, pipe 1000, drop 315, drop 630 and the lift station were 7.6, 6.2, 2.5, 8.01, 3.78 and 6.06 ppm, respectively. By utilizing a TOXCHEM model, the study helped to understand the fate and emission of hydrogen sulfide gas in all parts of the networks.